Employee Contextual Performance, Social Intelligence, Spiritual Intelligence: A quantitative Study in Malaysia - Choi Ling, Foo; Singh Kartar Singh, Jugindar; Arumugam, Thilageswary (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to examine the influence of social intelligence and spiritual intelligence towards the job performance of people. This was a quantitative study where a survey method was used to collect data from a sample of 140 respondents. Descriptive and inferential statistics were generated through the SPSS AMOS software. This study highlighted the importance of spiritual intelligence which can be applied effectively to improve performance of employees. However, the effect of social intelligence towards performance was not significant. From the practical implication's perspective, this study provided information to human resource specialists to include spiritual intelligence in their employee selection and development programs. These practices and interventions can lead to better performance of both employees and the organization. This was one of the first study in the services sector in Malaysia that demonstrated the value of spiritual intelligence and its implications on human resource policies and practices. It is suggested that spiritual intelligence be incorporated as a key component for organizational development.